Terapi Bermain Mewarnai sebagai Teknik Distraksi dalam Penurunan Ansietas Anak Sakit di Ruang Perawatan Anak RSUD Syech Yusuf - Eka, Eka Hadrayani (Journal of Community Engagement in Nursing, 2025)
Preschool-aged children undergoing hospitalization are vulnerable to anxiety due to changes in environment, medical procedures, and limited activity. If left unaddressed, anxiety can negatively impact the healing process and the child's psychosocial well-being. This community service activity aimed to implement coloring play therapy as a non-pharmacological distraction technique to reduce anxiety in hospitalized children. The intervention was conducted in the pediatric ward of RS Syekh Yusuf Gowa, involving seven children aged 3–6 years along with their parents or guardians. The method consisted of preparation, intervention implementation, observation of children's responses, and evaluation through parental reflection. The results indicated a significant improvement in children's moods; previously passive and anxious children became more relaxed, active, and demonstrated positive verbal and nonverbal interactions. Parental feedback also reflected strong support for the effectiveness of the activity. In addition to its direct benefits for children and families, this program provided a meaningful learning experience for the implementation team in applying therapeutic communication and observation skills within pediatric nursing practice. Coloring play therapy proved to be a simple, effective, and enjoyable intervention that can be integrated into pediatric nursing care in hospital settings. It is recommended that this intervention be applied regularly to enhance children's comfort and psychological well-being during hospitalization.